AN INVESTIGATION OF CONSOLIDANTS PENETRATION IN WOOD PART 2: FTIR SPECTROSCOPY - Timar, Maria Cristina; Tuduce Traistaru, Ana-Adriana; Patachia, Silvia; Croitoru, Catalin (Pro Ligno, 2011)
FTIR spectroscopy was used in this work for studying the penetration of some consolidants frequently used in old wood conservation into test pieces of sound spruce wood (Picea abies) wood. Thin microsections (30-60 µm) of control and treated wood were analysed in reflectance mode using an ATR system. The consolidation products investigated were Paraloid B72, bee wax, a mixture of bee wax / linseed oil and two types of paraffins. These products presented FTIR spectra with characteristic common and specific bands, allowing their identification in the treated wood with no impediments coming from their colour, transparency or the percent of cell lumena filling. The treatment of wood with these products brought about alterations of the spectra aspect by the appearance or intensification of some characteristic bands and the modification of the ratio between the areas of some characteristic absorption bands so that a qualitative and semi-quantitative evaluation of the presence and penetration depth and distribution of these consolidation products in wood was possible, proving the adopted method as valuable and useful for further research in this field.
Keywords: FTIR; consolidants; wood; characteristic absorption bands; index of consolidant retention